PENGEMBANGAN MODUL PELAKSANAAN KURIKULUM 2013 UNTUK MENINGKATKAN PROFESIONAL GURU ANAK USIA DINI - Radjiman Ismail (IAIN Ternate, 2020)
This research uses a research and development approach. The study aimed to develop early childhood teacher modules in developing learning devices following the conditions of the local area. Data collection techniques using questionnaires and Focus Group Discussion. Data analysis techniques using descriptive analysis and t-test. The research samples were early childhood teachers in Ternate city and early childhood education experts. The 2013 Early Childhood Education curriculum provides an opportunity for schools to develop learning models following the local context. Child learning starts from around the house and school so it is not uprooted from its cultural roots. In this curriculum, teachers are required to be able to develop their learning tools that are appropriate but on the other hand, there is a lack of books or modules that can be a guide in developing these learning devices. Based on this, the teacher module was developed as a practical guide in developing learning devices. Based on the results of the study, data from early childhood teacher modules was effectively used to improve the ability of teachers to develop learning devices. It is recommended that early childhood teachers in the urban area of Ternate be able to use this module to develop learning.